Blackbox Test on Web Based Employed Attendance Information System Design - Dinda Permana Srg, Dinda; Dedi Irawan, Muhammad (Ali Institute or Research and Publication, 2022)
The Hapesong New Village Office is a village asset building specifically designated for the operational activities of the Hapesong Baru Village government. The absence of employees at the Hapesong Baru Village office is an important and mandatory role for all employees to be used for official purposes in administration and administration. So far, the government of Batang Toru District, South Tapanuli Regency is still using the attendance system in a manual way that is still not computerized where employees must fill in attendance by writing down attendance signs for example the signature of the employee concerned, this way of attendance has the risk of committing fraud. quite large, because there is still an opportunity to fake employee attendance signs. Data accumulation and errors often become obstacles in processing employee attendance data. Therefore, the authors chose Batang Toru District, South Tapanuli Regency as the object of research. With the development of digital technology, one of which is in the field of computerization, it can help the system in employee attendance. The result of this research is the Design of an Employee Attendance Information System at the Web-Based Hapesong Baru Village Office. In making attendance attendance applications, which are built using a programming language, on the server side is PHP while on the client server side it is HTML. In the database using SQL language with MYSQL DBMS. The modeling of this expert system uses the Unified Modeling Language model.